Evaluasi Implementasi Cara Produksi Pangan Yang Baik (CPPB) Untuk Industri Rumah Tangga Produksi Bolen - Fadhila, Rahmah; Maksum, Mochammad; Supartono, Wahyu (JURNAL AGROINDUSTRI HALAL, 2024)
Efforts to obtain safe and quality food include good food processing and management of a clean production environment. Implementation of good production by applying the CPPB-IRT food safety assurance system as a processing guideline. The basis of analysis uses 14 aspects, namely location and production environment, buildings and facilities, production equipment, facilities for providing water, sanitation facilities and practices, employee health and hygiene, maintenance and hygiene and cleanliness programs, storage, process control, food labeling, supervision from the person in charge, product recall, recording and documentation, and employee training. The research data collection used observation, interviews, checksheet filling and literature study. The results of the analysis based on BPOM regulation No. HK.03.1.23.04.12.2206 stated that CPPB-IRT in bolen production achieved a percentage conformity of 86.6% and a non-conformity of 13.4%. The assessment of non-conformity is found in the criteria in several aspects following the criteria from the aspects of buildings and facilities, employee health and hygiene, maintenance and cleaning and sanitation programs, storage, supervision by the person in charge, product recall, recording and documentation. The results of the analysis of BPOM regulation No. HK.03.1.23.04.12.2207 state that there are 4 out of 14 aspects of CPPB-IRT bias, namely in the aspects of buildings and facilities, employee health and hygiene, supervision by the person in charge, recording and documentation. Deviations in the implementation of GMP can be a reference for policy makers in creating regulations or strategies so that SMEs are able to implement GMP thoroughly